Comorbidities associated with reduced myocardial flow reserve in non-obstructive disease. (14th October 2021) - Gurrola-Luna, H; Rojas-Sernaque, J K; Barajas Paulin, A J; Carvajal-Juarez, I; Bermudez-Gonzalez, J L; Rivera-Bravo, B; Soto-Lopez, M E; Garcia-Arroyo, A J; Cuellar-Vargas, J K; Arce-Sandoval, C R; Zavala-Romero, L; Romero-Montiel, R E; et al.
Abstract: Introduction: Microvascular Dysfunction defined as a Myocardial Flow Reserve (MFR) <2 or <2.5 depending on the center, may present in the absence of significant obstruction (1, 2); it is included as a diagnosis criteria of Microvascular Angina (MVA) (3, 4) and is an independent risk factor associated with poor prognosis (5–7). Traditional Coronary Artery Disease (CAD)risk factors have also been associated with MVA (8–10), however, there is reduced data in latin populations with high prevalence of comorbidities. The aim of this study was to identify the comorbidities that alter MFR with 13N-ammonia Positron Emission Tomography/Cardiac Tomography (PET/CT) and Cardiac Computed Tomography Angiography (CCTA) in a cardiovascular imaging referral center. Methods: Retrospective cross-sectional study of patients with suspected CAD in which both PET/CT and CCTA were performed. Inclusion:CCTA with obstruction <50%. Exclusion: incomplete study, previous infarction or intervention. Clinical data was assessed. Mean (±DE) or median (interquartile range) to present continuous variables according to their distribution; T student or U Man Whitney to compare them. For each variable two groups were conformed depending on its presence or absence in order to compare MFR between them. Statistical analysis was performed with Statistical Package for Social Science (SPSs Inc, Chicago, IL; version 23.0) and GraphPad Prism version 9.0. p<0.05 was considered as significant. Results: 335 patients included. MFR difference for each variable: female sex, hypertension (HT), Type 2 diabetes (T2D) and smoking – Appendix 1. Significant MFR difference for HT (p=0.024) and T2D (p=0.046). Severe ischemia had significant MFR reduction (p=0.006); patients with both HT and mild ischemia (p=0.018) – Appendix 2. Discussion: Individuals with HT and T2D had a significantly lower MFR, consistent with previous studies (8, 9). Absence of correlation with other risk factors, such as smoking (10) and female sex (11); latter may be caused by a significant lower number of women (108 vs 227). Further analysis in this subgroup ought to be done. When comparing MFR between level-of-ischemia groups, microvascular function was not reduced until severe ischemia. Remarkably, if we analyze the coexistence of HT with ischemia, MFR is reduced even in patients with mild ischemia. This finding highlights the importance of HT which alters function in early stages even in the absence of significant obstruction. This is one of the first studies correlating MFR with comorbidities in our population. Limitations the retrospective nature of the study. Conclusions: MFR non-invasive assessment by PET/CT allows identifying very early stages of MVD, even in asymptomatic patients and when there's no evidence of ischemia or CAD. Therefore, timely recognition of this problem is mandatory to implement action strategies to stop the triggered events' cascade. Funding Acknowledgement: Type of funding sources: None.